Identification of Koi Herpesvirus on Koi Fish (Cyprinus carpio) with Immunocytochemistry Test Streptavidin Biotin - Rika Wahyuningtyas; Uun Yanuhar (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2018)
Koi herpesvirus (KHV) has been identified in common carp (Cyprinus carpio) and varieties of C. carpio such as koi carp. Handling KHV outbreak on koi fish are always late and on case KHV infection, hence the purpose of this study is to find an alternative method in identifying a particular fish diseases KHV which more simple, practical and accurate. 20 samples are positively infected by KHV were derived from Blitar, with the characteristic of them are gill slime, erosion or ulcers on the skin, movement were not controlled, and skin blister. The result of our study showed that 100% positive reaction to the ICC in smear blood, which is marked golden chocolate color. The result of immunostaining streptavidin biotin obtained that koi fish have been infected by severe KHV showed golden chocolate color on the blood smear compared to positive control. While fish have been infected by undemanding KHV infection or still in the beginning stage, the blood smear showed chocolate bluish. It can be concluded that Immunocytochemistry Test Streptavidin Biotin can be used for early identifying of Koi Herpes Virus (KHV) due to simpler producer, more practical, and accurate result.